Identifying competitive strategies for each phase of the intermodal terminal life cycle. (June 2017) - Monios, Jason; Bergqvist, Rickard
Abstract: This paper applies the marketing strategy literature to the four phases of the intermodal terminal life cycle (ITLC) to identify the appropriate competitive strategy to be undertaken at each phase, based on fluctuating markets and competitor behaviour. Not only can applying the correct strategy at each phase help to obtain a competitive advantage, but anticipating future strategies in advance can underpin the success of current strategies and ensure that both public and private stakeholders are prepared for future challenges. The paper derives the appropriate strategies, provides empirical examples and discusses the opportunities and challenges inherent in each strategy. The paper concludes with suggestions for future research on strategy options that go beyond the traditional view of terminals as homogeneous interchangeable assets. Rather than simple improvement of factor conditions by investing in the infrastructure, innovative strategies to obtain competitive advantage should focus on partnerships with external stakeholders such as rail operators, 3PLs and shippers.